College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 1 - Equations and Inequalities - Exercise Set 1.2: 78

Answer

x=3 conditional equation

Work Step by Step

$\frac{1}{x-1}$=$\frac{1}{(2x+3)(x-1)}$+$\frac{4}{2x+3}$ 2x+3=1+4x-4 2x=6 x=3 There is one solution so it is a conditional equation.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.